تسوية المنازعات الضريبية أمام القضاء الإداري - عربوز, فاطمة الزهراء (جامعة الوادي University of Eloued, 2017)
يكتسي موضوع المنازعة الضريبية أهمية كبيرة على الصعيد العملي؛ نظرا للانتشار المتزايد لهذا النوع من المنازعات أمام القضاء، وذلك نتيجة التدخل المستمر من قبل مصلحة الضرائب بحكم وظيفتها في خوض وتحصيل الضرائب. وتتميز المنازعة الضريبية عن غيرها من المنازعات الإدارية بطابع خاص؛ حيث تتطلب السرعة في البث والخبرة والدراية بالشؤون المالية، إضافة إلى السرّية لما تتضمنه من حماية للمال العام والذّمة الخاصة، لذلك أفرد لها المشرع الجزائري أحكاما خاصة وردت أساسا في قانون الإجراءات الجبائية، وأخرى في قانون التسجيل، وكذا في قانون الضرائب المباشرة والرسوم المماثلة، كما وضع الآليات والضمانات التي تكفل للمكلف بالضريبة الطعن في قرارات إدارة الضرائب في حالة عدم رضاه بها، ورسم له طريقين طريق إداري وهو إلزامي يسلكه المكلف أمام الإدارة الضريبية، وطريق آخر قضائي، والذي يتمّ عن طريق الدعوى الضريبية باعتبارها الوسيلة أو الممكنة التي يخولها القانون للمكلف في اللجوء إلى القضاء الإداري للمطالبة بحقوق مستها تصرفات وأعمال إدارة الضرائب وأضرت بها، ولاشك أن الرقابة القضائية هي أكثر الضمانات فعالية لحماية حقوق المكلف بالضريبة كونه الطرف الضعيف في العلاقة الضريبية. Abstract: The subject of tax dispute is of great importance at the practical level, due to the increasing prevalence of this type of dispute before the courts and as a result of continuing intervention from tax authorities by virtue of their function in the search and collection of taxes. The tax dispute is regarded as a distinctive one compared to other administrative disputes, as it requires speed of treatment, experience and knowledge of financial affairs as well as confidentiality to prevent disclosure of public money and private liability; therefore the Algerian legislature allocated special provisions contained mainly in the code of fiscal procedures, the registration code and the direct taxes and similar taxes law; it also put in place the necessary mechanisms and safeguards that guarantee to the taxpayer appeal against tax administration decisions; two paths are made available for this purpose : an administrative way which is mandatory before the tax administration, and a judicial pathway that is through tax lawsuit which is the course and action conferred by the law to the taxpayer to have recourse to the administrative court and claim his rights affected by conduct and tax administration acts; there is no doubt that the judicial control is the most effective way to protect taxpayer rights as he is the most vulnerable party in tax relationships.
Keywords: المنازعات الضريبية؛ القضاء الإداري؛ مصلحة الضرائب؛ الدعوى الضريبية؛ الخبرة؛ مجلس الدولة